2022
DOI: 10.1186/s12951-022-01437-2
|View full text |Cite
|
Sign up to set email alerts
|

Three birds with one stone: co-encapsulation of diclofenac and DL-menthol for realizing enhanced energy deposition, glycolysis inhibition and anti-inflammation in HIFU surgery

Abstract: Despite attracting increasing attention in clinic, non-invasive high-intensity focused ultrasound (HIFU) surgery still commonly suffers from tumor recurrence and even matastasis due to the generation of thermo-resistance in non-apoptotic tumor cells and adverse therapy-induced inflammation with enhanced secretion of growth factors in irradiated region. In this work, inspired by the intrinsic property that the expression of thermo-resistant heat shock proteins (HSPs) is highly dependent with adenosine triphosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…They revealed that lactate significantly declined along with ATP. Wu et al reported that inhibiting glycolysis can sensitize tumor cells to high-intensity focused ultrasound (HIFU) thermal therapy . The possible reason is that thermo-resistant heat shock proteins (HSPs) are downregulated, and the synthesis of HSPs is highly ATP-dependent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They revealed that lactate significantly declined along with ATP. Wu et al reported that inhibiting glycolysis can sensitize tumor cells to high-intensity focused ultrasound (HIFU) thermal therapy . The possible reason is that thermo-resistant heat shock proteins (HSPs) are downregulated, and the synthesis of HSPs is highly ATP-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…As such, the cancer cells became more vulnerable and less tolerant to MW-mediated hyperthermia and dynamic therapy. A similar mechanism was proposed in a previous study by Wu et al The histological examination with H&E staining showed that the tumor death in the HFM@SK@HA + MW group was more radical as compared with the other treatment groups (Figure F). As displayed in Figure E, the weight change of mice in each group was not obvious.…”
Section: Resultsmentioning
confidence: 99%
“…The released DA inhibits COX-2 activity and blocks arachidonic acid conversion to PGE 2 . [39][40][41] Blocking the COX-2/PGE 2 pathway could both decrease pro-tumor inflammatory factors including IL-6 and TNF-đ›Œ and further down-regulate the PD-L1 expression to reduce the tumor cells inhibition by cytotoxic T cells. In general, CCP@DA induced a strong ICD to activate anti-tumor immunity through targeted photothermal/photodynamic synergistic therapies on the tumor cell membrane.…”
Section: Introductionmentioning
confidence: 99%
“…In order to restrain glycolysis, the utilization of chemotherapy drugs has aroused great attention. 20,21 However, as mentioned above, there are numerous challenges faced by chemotherapy, such as MDR. Exceptionally, researchers have certified that although some glycolysis related proteins could be destroyed during the treatment, the mitochondria could also play a vital role in providing energy for cytoprotection.…”
Section: Introductionmentioning
confidence: 99%